2006
DOI: 10.1017/s1368980006009931
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the nutritional status of children aged 0–5 years in a drought-affected desert area of western Rajasthan, India

Abstract: Objective: The present study was undertaken to assess the impact of drought on the nutritional status of pre-school children aged 0-5 years from a rural population in a desert area facing drought conditions very frequently. Design: The sampling design for assessment was the three-stage sampling technique. Setting: The study was carried out in 24 villages belonging to six tehsils (sub-units of district) of Jodhpur District, a drought-affected desert district of western Rajasthan, during a drought in 2003. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 3 publications
10
35
3
Order By: Relevance
“…Solomon and Amare (2013) have reported 42.3% of wasting, 34.4% of stunting and 47.7% of underweight in Dolo Ado district of Somali region South of Ethiopia while Yalew (2014) has indicated stunting, wasting and underweight in the order of 44%, 29% and 10% respectively in Lalibela, Amhara regional state, Northern Ethiopia [12,13]. The chronic malnutrition rates in our study are quit in agreement with a number of other studies while the findings on the acute malnutrition rates are higher than previous reports [9,10,[12][13][14][15]. This can be associated to the fact that our study community were under a continued food and nutrition security problem where two consecutive rains failed [16].…”
Section: Factors Of Child Malnutritionsupporting
confidence: 91%
See 1 more Smart Citation
“…Solomon and Amare (2013) have reported 42.3% of wasting, 34.4% of stunting and 47.7% of underweight in Dolo Ado district of Somali region South of Ethiopia while Yalew (2014) has indicated stunting, wasting and underweight in the order of 44%, 29% and 10% respectively in Lalibela, Amhara regional state, Northern Ethiopia [12,13]. The chronic malnutrition rates in our study are quit in agreement with a number of other studies while the findings on the acute malnutrition rates are higher than previous reports [9,10,[12][13][14][15]. This can be associated to the fact that our study community were under a continued food and nutrition security problem where two consecutive rains failed [16].…”
Section: Factors Of Child Malnutritionsupporting
confidence: 91%
“…Thirty percent of the children studied had MUAC less than 11.5cm which is the cutoff point recommended by WHO for public health emergency interventions. Mason, et al (2012) and Singh, et al (2006) have similarly reported high malnutrition rates in children in households affected by drought and conflicts [9][10][11]. Solomon and Amare (2013) have reported 42.3% of wasting, 34.4% of stunting and 47.7% of underweight in Dolo Ado district of Somali region South of Ethiopia while Yalew (2014) has indicated stunting, wasting and underweight in the order of 44%, 29% and 10% respectively in Lalibela, Amhara regional state, Northern Ethiopia [12,13].…”
Section: Factors Of Child Malnutritionmentioning
confidence: 99%
“…The incidences of undernutrition obtained in the present study were found to be distinctly lower than those among tribal children of Madhya Pradesh (51.6% stunting, 61.6% underweight and 32.9% wasted) as documented by Rao et al (2005) and among children of Rajasthan (53% stunting, 60% underweight and 28% wasted) as reported by Singh et al (2006). Similarly, the incidences of wasting in present studied boys and girls were found to be lower than the values reported from West Bengal (13.94%) and Assam (14.42%) by Som et al (2006).…”
Section: Discussioncontrasting
confidence: 47%
“…frequent occurrence of drought, low rainfall and high temperature, which affect the economy and food intake of the inhabitants (15,16) . According to WHO (1) , at present, iron and vitamin A supplementation are the most common strategies currently used to control these deficiencies in developing countries for the time being.…”
Section: Discussionmentioning
confidence: 99%